Feasibility, use and benefits of patient-reported outcome measures in palliative care units: a multicentre observational study - Müller, Evelyn; Mayer-Steinacker, Regine; Gencer, Deniz; Alt-Epping, Bernd; Schönsteiner, Stefan; Jäger, Helga; Couné, Bettina; Elster, Luise; Keser, Muhammet; Rauser, Julia; Marquardt, Susanne; Becker, Gerhild (BMC palliative care, 2023)
Research has shown that routinely assessed, patient-reported outcome measures (PROMs) have positive effects in patients with advanced oncologic diseases. However, the transferability of these results to specialist palliative care is uncertain because patients are more impaired and staff doubt the feasibility and benefits. The aim of this study is to evaluate the feasibility of patient self-assessment of PROMs, their use by staff and the benefits in palliative care wards.
Gesehen am 18.04.2023